Arctic methylmercury cycling - Jonsson, Sofi; Nerentorp Mastromonaco, Michelle; Wang, Feiyue; Bravo, Andrea G.; Cairns, Warren R.L.; Chételat, John; Douglas, Thomas A.; Lescord, Gretchen; Ukonmaanaho, Liisa (Science of The Total Environment, 2022)
21 pages, 6 figures, 2 tables, supplementary data https://doi.org/10.1016/j.scitotenv.2022.157445 Anthropogenic mercury (Hg) undergoes long-range transport to the Arctic where some of it is transformed into methylmercury (MeHg), potentially leading to high exposure in some Arctic inhabitants and wildlife. The environmental exposure of Hg is determined not just by the amount of Hg entering the Arctic, but also by biogeochemical and ecological processes occurring in the Arctic. These processes affect MeHg uptake in biota by regulating the bioavailability, methylation and demethylation, bioaccumulation and biomagnification of MeHg in Arctic ecosystems. Here, we present a new budget for pools and fluxes of MeHg in the Arctic and review the scientific advances made in the last decade on processes leading to environmental exposure to Hg. Methylation and demethylation are key processes controlling the pool of MeHg available for bioaccumulation. Methylation of Hg occurs in diverse Arctic environments including permafrost, sediments and the ocean water column, and is primarily a process carried out by microorganisms. While microorganisms carrying the hgcAB gene pair (responsible for Hg methylation) have been identified in Arctic soils and thawing permafrost, the formation pathway of MeHg in oxic marine waters remains less clear. Hotspots for methylation of Hg in terrestrial environments include thermokarst wetlands, ponds and lakes. The shallow sub-surface enrichment of MeHg in the Arctic Ocean, in comparison to other marine systems, is a possible explanation for high MeHg concentrations in some Arctic biota. Bioconcentration of aqueous MeHg in bacteria and algae is a critical step in the transfer of Hg to top predators, which may be dampened or enhanced by the presence of organic matter. Variable trophic position has an important influence on MeHg concentrations among populations of top predator species such as ringed seal and polar bears distributed across the circumpolar Arctic. These scientific advances highlight ...